Production process and characterization of extra cellular li-pids from bacterial strain from oil industries waste - Balamurugan, Vadivel; Balakrishnan, Veluchamy; Sundaresan, Arjunan; Vasanthi, Kodhandapani; Venkatesan, Selvaraj (International Journal of Biological Research, 2016)
The Bacillus sp was isolated from oil industry waste. The isolated strain was screened for the production of lipase enzyme. The production was done by shake flask fermentation. After downstream processing, the partial purification was done my ammonium sulphate precipitation & dialysis and the assay was done by photometric method. The various factors affecting production of extra cellular lipase activity was assayed which include pH, different substrate, temperature and additives. Besides, production was made using different carbon source and crude medium. Result showed that pH 6 and 37Â°C is an optimum environmental parameter for the growth of the isolate. In addition, the sucrose was found to be better carbon source.
Keywords: Bacillus species; Bacterial strain; Extra cellular lipids; lipase enzyme; Oil industries waste.